2021
DOI: 10.3390/ma14216715
|View full text |Cite
|
Sign up to set email alerts
|

Snow Melting Performance of Graphene Composite Conductive Concrete in Severe Cold Environment

Abstract: The use of conductive concrete is an effective way to address snow and ice accretion on roads in cold regions because of its energy saving and high efficiency without interruption of traffic. Composite conductive concrete was prepared using graphene, carbon fiber, and steel fiber, and the optimum dosage of graphene was explored with resistivity as the criterion. Subsequently, under the conditions of an initial temperature of −15 °C and a wind speed of 20 km/h, the extremely severe snow event environment in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Other researches [28,38,45] have confirmed that the origin of electrically conductive additives has a different impact on electrical properties of mineral composites.…”
Section: -391 the Study Of The Properties Of Nanomaterialsmentioning
confidence: 94%
See 2 more Smart Citations
“…Other researches [28,38,45] have confirmed that the origin of electrically conductive additives has a different impact on electrical properties of mineral composites.…”
Section: -391 the Study Of The Properties Of Nanomaterialsmentioning
confidence: 94%
“…The impact of different man-made materials with electrically conductive particles on mineral matrices have been esteemed for the following materials: carbon black [28], asphaltene [35], steel shaving [34], slag [37], industrial carbon [42], fly ash [38], powdered coke [43], carbon-contained slag from aluminum production [2]. All that researches have provided enough data to make a conclusion that the impact of morphology, size of particles and distribution on structure formation is much more significant than the role of the content.…”
Section: -391 the Study Of The Properties Of Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, deicing technologies include conductive concrete [ 1 , 2 , 3 ], circulating heating systems [ 4 , 5 , 6 ], electric cable heating [ 7 ], solar energy [ 8 ], geothermal systems [ 9 , 10 ], induction heating, microwave heating [ 11 ], etc. Compared with the above deicing technologies, self-ice-melting asphalt pavements with salt-storage additives have the advantages of relatively low cost and easy construction.…”
Section: Introductionmentioning
confidence: 99%
“…Materials with good conductivity, such as steel fiber [16,17], carbon fiber [18,19], erosion wire [20], steel shaving [16], graphite powder [13,21], carbon nanotube [22], carbon black [20] and graphene [23] can be used to increase the electrical conductivity of cementitious materials. Fig.…”
Section: Introductionmentioning
confidence: 99%